Bariatric Triage: Weight Loss As A Tool For Therapeutic Decision Making - Sanjay Kalra; Jubbin Jacob; Nitin Kapoor (Journal of the Pakistan Medical Association, 2023)
This communication highlights how early weight loss can be used as a technique for triage in persons who have undergone bariatric surgery, and as a tool for therapeutic decision making. Weight loss is a target for obesity medicine, but can also be used to plan further treatment strategies and interventions. In this manner, early weight loss is similar to HbA1c (glycated haemoglobin) which is a diagnostic tool, a monitoring device, a therapeutic target, and also a technique to decide intensity of treatment in diabetes. Keywords: Bariatric triage, barocrinology, metabolic, adaptation, obesity, overweight.